Educación, virtualidad e innovación Estudio de caso para la consolidación de un modelo de liderazgo en la educación incluyente y de calidad - Leal Afanador, Jaime Alberto (Sello Editorial UNAD, 2021)
This book aims to highlight the educative evolution that Universidad Nacional Abierta y a Distancia - UNAD (National Open and Distance University) has promoted since its foundation, based on the distance learning paradigm, and growing despite the resistance created with traditional education. We present the techno-pedagogical keys of virtual education, new paradigms, and alternative learning models. We explored the Pedagogical Unadista Model (MPU, for its Spanish acronym); the sense and meaning of the learning assessment; the teaching role of the educational tools and resources as knowledge support; as its planning phases and own instruments of virtual education, explaining the Teacher's role in this educational model, in particular of the UNAD. The evolution and historical context of the UNAD, how it accomplished stabilization and routing to become the Colombian mega University and provide the foundation for today's University's future. We assessed the need to change the University as a social organization to regain its previous leadership regarding global alerts. In this context, we evaluated the detachment from orthodox and bureaucratic ways in which public administration performs within a framework of limited effectiveness when accountability on social impact. The book's title, "Educación Virtual e innovación" (Virtual Education and Innovation), is based on the simplest definitions of the components of the meta-system called UNAD. This to clarify the business process reengineering, which was used as a significant opportunity to rebuild a public university with a modern disposition, committed to the pursuit of educational excellence extensive for all. And thereby strongly influence in the hope of creating access opportunities and educational validity for Colombia and Latin America.